Explicit Grammar Instructions Enhance Students’ Reading Ability on Cognitive Aspect - Aprizani, Yudha; Islamiah, Neneng; Furyanto, Faoyan Agus (Master Program in Linguistics, Diponegoro University, 2018)
This research aimed to find out the result of comparison between experimental and control group whether explicit instruction has influence in enhancing student’s cognition in language grammar on reading skills at MTS Al Muddakir Banjarmasin. The number of participants taken by researcher are 20 students either experimental and control group. The collecting of data used by researcher is to apply an essay test and reading texts. Researchers build up the test of instrument validity and reliability before the instruments are tested in experimental group. Then, researcher did independent sample t-test untuk find out the mean score of cognitive ability of students in language grammar on reading skills. The result of finding gained by research stated that sig (2-tailed) 0.000 is less than 0.05. it meant that there is difference of influencing cognitive ability of students in language grammar on reading skills but in independent sample t-test, the result is 0.164 > 0,05. It can be concluded that it meant that there is no difference of mean score of cognitive ability of students on experimental group but for the influence of explicit instruction that resulted in paired sample t-test, there is difference of influencing the result of cognitive ability of students in reading skills.